Invasive Endocervical Adenocarcinoma. (May 2015) - Roma, Andres A.; Diaz De Vivar, Andrea; Park, Kay J.; Alvarado-Cabrero, Isabel; Rasty, Golnar; Chanona-Vilchis, Jose G.; Mikami, Yoshiki; Hong, Sung R.; Teramoto, Norihiro; Ali-Fehmi, Rouba; Rutgers, Joanne K.L.; Barbuto, Denise; et al.
<x xml:space="preserve">Abstract</x> A new 3-tier pattern-based system to classify endocervical adenocarcinoma was recently presented. In short, pattern A tumors were characterized by well-demarcated glands frequently forming clusters or groups with relative lobular architecture. Pattern B tumors demonstrated localized destructive invasion defined as desmoplastic stroma surrounding glands with irregular and/or ill-defined borders or incomplete glands and associated tumor cells (individual or small clusters) within the stroma. Tumors with pattern C showed diffusely infiltrative glands with associated extensive desmoplastic response. In total, 352 cases (all FIGO stages) from 12 institutions were identified. Mean patient age was 45 years (range, 20 to 83 y). Forty-nine (13.9%) cases demonstrated lymph nodes (LNs) with metastatic endocervical carcinoma. Using this new system, 73 patients (20.7%) were identified with pattern A tumors (all stage I); none had LN metastases and/or recurrences. Ninety patients (25.6%) were identified with pattern B tumors (all stage I); only 4 (4.4%) had LN metastases; 1 had vaginal recurrence. The 189 (53.7%) remaining patients had pattern C tumors; 45 (23.8%) of them had LN metastases. This new classification system demonstrated 20.7% of patients (pattern A) with negative LNs, and patients with pattern A tumors can be spared of lymphadenectomy. Patients with pattern B tumors rarely presented with metastatic LNs, and sentinel LN examination could potentially identify these patients. Aggressive treatment is justified in patients with pattern C tumors.